PERSEPSI PELAJAR-PELAJAR UNIVERSITI MALAYSIA SARAWAK TERHADAP PEMBELAJARAN MENGGUNAKAN INTERNET - Mahadi, Kasdi (Universiti Malaysia Sarawak, (UNIMAS), 1997)
The purpose of this study is to identify the perception of Unimas' students towards learning via the Internet. The objectives of the research are (a) describing the demographic features of respondents, (b) determining the perception of Unimas' Students toward learning using the Internet, (c) determining relationships between the academic environment and perception of Unimas' students, (d) determining relationship between behaviours and perception of Unimas' students, (e) determining the differences in perception based on some selected demographic features. A total number of 120 respondents from 8 faculties in Universiti Malaysia Sarawak were chosen as the sample for this study. Questionnaires consisted 30 Four-Point Likert Scale items were used to measure the perceptions of respondents consists towards knowledge acquisition via the Internet. A descriptive statistical method frequency of percentage, and mean was used for measuring and summarizing the demographic features of respondents. For the purpose of this study, 2 main hypotheses and 1 1 specific hypotheses were formulated. These hypotheses were then tested using statistical analysis such as Pearson Correlation, t-test and One- Way Analysis of Variance (ANOVA). The findings showed that the perceptions of Unimas' students toward learning using the Internet were moderate. Test of hypotheses produced the following results (a) there were significant relationships between the academic environment and perception of the students, (b) there were significant relationships between behaviours and perception of the students, (c) there were significant differences in perception among Unimas' students based on demographic features such as gender, age, faculty, marital status, year of study, students' academic level, and their fathers' academic levels, except for some factors such as race, education sponsorships, their mothers' educational levels and parents' income. Generally, the research findings had revealed that the perceptions of the Unimas' students toward learning via the Internet were mainly influenced by the environment and their own selves. The prevailing degree of perceptions need to be improved to a higher level in conformance with the university's expectations and demands of the current digital information era